Analisis Pengaruh Kualitas Layanan, Fasilitas, Harga dan Lokasi Terhadap Kepuasan Konsumen di Premier Futsal Kediri - Meswanto; Djunaidi; Angga Rizka (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to determine the effect of service quality, facilities, price, and location on customer satisfaction at Premier Futsal Kediri. This type of research uses a quantitative method, namely a method that describes in detail about something that is the object of research. The population in this study was the number of visitors to Premier Futsal Kediri in June 2022, which amounted to 960 people and a sample of 100 respondents. The sampling technique was convenience/accidental sampling. The data collection method used a questionnaire, observation, documentation, and literature study. The data analysis method used validity and reliability tests, classical assumption tests, multiple linear regression tests, partial significance tests (t-statistic tests), simultaneous significance tests (f-statistic tests), and coefficients of determination. From the results of this study, it can be concluded that: (1) Service quality (X1), facilities (X2), price (X3), and location (X4) together (simultaneously) have a relationship with the dependent variable, namely customer satisfaction (Y). (2) Partial service quality does not have a significant relationship with the customer satisfaction variable. This can be proven by the results of the t count of -0.552 smaller than the t table of 0.677 with a significance level of 0.582 greater than 0.050.